2019
DOI: 10.1080/21505594.2019.1700659
|View full text |Cite
|
Sign up to set email alerts
|

Wza gene knockout decreases Acinetobacter baumannii virulence and affects Wzy-dependent capsular polysaccharide synthesis

Abstract: To investigate the virulence of capsular polysaccharide export protein (Wza) in carbapenemresistant Acinetobacter baumannii and its effect on capsule formation. wza gene knockout and complementation strains were constructed, and changes in bacterial virulence were observed using in vitro adhesion, antiserum complement killing, anti-oxidation experiments, and infections in Galleria mellonella and mice. The effect of wza knockout on the genes wzb and wzc and wzi were assessed by RT-PCR. We successfully construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 54 publications
2
38
1
Order By: Relevance
“…The CPS of different isolates are linear or branched and may possess non-carbohydrate substituents, including the most frequent O - and N -acyl groups [ 44 ]. The Wzy pathway encoded by the K locus is responsible for the export and extracellular assembly of CPS [ 45 ]. The K locus is regulated by the two-component signal transduction system BfmRS.…”
Section: A Baumannii and The Host Innate Immunmentioning
confidence: 99%
See 2 more Smart Citations
“…The CPS of different isolates are linear or branched and may possess non-carbohydrate substituents, including the most frequent O - and N -acyl groups [ 44 ]. The Wzy pathway encoded by the K locus is responsible for the export and extracellular assembly of CPS [ 45 ]. The K locus is regulated by the two-component signal transduction system BfmRS.…”
Section: A Baumannii and The Host Innate Immunmentioning
confidence: 99%
“…Several studies demonstrated that the production of capsules affects A. baumannii virulence and persistence in the host [ 50 , 51 ]. Capsule-enriched strains cause more severe disease or higher lethality [ 35 , 45 , 50 , 52 , 53 ]. These observations may be partly explained by the high hydrophilicity of CPS and negative charges of CPS monosaccharides that prevent phagocytosis by hindering interactions with the negatively charged surfaces of neutrophils and macrophages, preventing phagocytosis [ 35 ].…”
Section: A Baumannii and The Host Innate Immunmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to form capsule is considered as an important virulence trait in bacteria, together with resistance to antibiotics, biofilm formation, adhesiveness, desiccation, and other features [ 35 , 36 , 37 ]. The role of capsular exopolysaccharides in S. maltophilia virulence is still unknown.…”
Section: Resultsmentioning
confidence: 99%
“…The ability to produce exopolysaccharide capsule is indicative of a strain’s ability to avoid killing by a host’s immune system [ 36 , 38 ]. We aimed to test if isolates differed in their ability to survive serum-mediated killing.…”
Section: Resultsmentioning
confidence: 99%